2013
DOI: 10.5901/mjss.2013.v4n11p631
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Schools’ Efficiency of Different Educational Systems

Abstract: The allocation of public resources is an important concern of developed economies in modern societies and there are many studies that aim at measuring their efficiency. This work presents an efficiency assessment of public elementary schools in Andorra, a little country where there are three public educational systems (Andorran, Spanish -congregational and non congregational-, and French). Therefore, the aim of this study is to compare the efficiency of public elementary schools among the three different educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…As discussed, DEA can be used to assess educational efficiency [23,30]. Chang et al (2012) applied DEA to evaluate allocated education resources [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As discussed, DEA can be used to assess educational efficiency [23,30]. Chang et al (2012) applied DEA to evaluate allocated education resources [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Si bien a nivel internacional existen varios estudios (Grosskopf et al 2001;Banker et al 2004;Blackburn et al 2013;Casalprim et al 2013 señalarían que el centro es ineficiente y por tanto la cuantía de la ineficiencia indica la cantidad de output que podría ser aumentado si se eliminara la ineficiencia.…”
Section: Revista De Evaluación De Programas Y Políticas Públicasunclassified
“…It is concluded that characteristic of students and the family environment are major factors that influence school performance in Oklahoma. The paper [7] presents examining the efficiency of public primary schools in Andorra. 25 primary schools with different educational systems are analysed for a period of 5 years.…”
Section: Introductionmentioning
confidence: 99%